Optimal Coupling of Hepatic Mitochondrial Metabolism with Lipogenesis Promotes Healthy Embryonic to Post-hatch Development in Chicken (FS03-01-19). (13th June 2019) - Surugihalli, Chaitra; Chan, Angela; Maguire, Meghan; Farley, Linda; Liu, Hsiao-Ching; Porter, Tom; Sunny, Nishanth
Abstract: Objectives: With 90% of the energy derived from yolk lipid oxidation in late-term embryos, and the dramatic induction of lipogenesis post-hatch, the liver is subjected to intense lipid burden during embryonic to post-hatch transition in chicken. Interestingly, unlike in rodents and humans with non-alcoholic fatty liver disease, this metabolic milieu in chicken embryos and hatchlings is not thought to promote metabolic syndrome or oxidative stress. We hypothesized that the optimal coupling of hepatic mitochondrial oxidative metabolism and lipogenesis will support insulin signaling and prevent onset of oxidative stress. Methods: Fertile eggs (64 ± 3 g) were incubated at 38 °C and 45% relative humidity. At embryonic days (e), e14, e18 and post-hatch days (ph), ph3 and ph7, serum and tissues were collected for metabolic analysis. Hepatic mitochondria was isolated and incubated with [ 13 C3 ]pyruvate to determine tricarboxylic acid (TCA) cycle activity and reactive oxygen species (ROS) production. Results: Serum ketones (µM ± SEM) were significantly higher ( P  < 0.01) during e14 (3237 ± 189) and e18 (3944 ± 503) and reduced dramatically after hatch (ph3; 381 ± 42, ph7; 322 ± 60). Conversely, hepatic triglycerides (mg/g ± SEM) significantly increased from e14 (2.3 ± 0.6) and e18 (7.4 ± 1.2) to ph3 (93.6 ± 11.79) and ph7 (92 ± 14). Genes regulating lipid oxidation and lipogenesis paralleled the changes in ketones and liver triglycerides respectively. Further, hepatic mitochondrial activity during e18 and ph3 was significantly higher compared to e14, as determined by the rates of 13C incorporation into the TCA cycle intermediates. Interestingly, lipotoxic intermediates (ceramides, diacylglycerols) and inflammatory markers (IL6, TNFA) remained unchanged through e14 to ph7, while ROS production decreased from e14 to ph7. Phosphorylation rates of AKT in the liver was progressively higher from e14 through ph7, suggesting robust insulin signaling. Conclusions: These results illustrate optimal coupling between mitochondrial oxidative metabolism, lipogenesis and insulin signaling, thus preventing the onset of oxidative stress during embryonic to post-hatch development. Embryonic to neonatal transition in chicken could be a valuable model to investigate mechanisms regulating mitochondrial lipid oxidation, lipogenesis and onset of hepatic insulin resistance. Funding Sources: National Institutes of Health.